Psychogenic Blindness: A Rare Presentation - Dutta, A; Poudel, R; Thapa, LJ; Pokhrel, B (Journal of Psychiatrists’ Association of Nepal, 2014)
Psychogenic blindness is a type of dissociative sensory loss which is characterized by unilateral or bilateral loss of vision/poor vision in the absence of any organic cause. We present a case of psychogenic blindness in a 21 years old female, 32 weeks primigravida who had presented with both eye complete loss of vision of 6 days duration. On admission , ophthalmological and neurological examination revealed no abnormality of visual pathways . Psychoeducation and reaasurance lead to complete visual recovery after 12 hrs of first psychiatric intervention. DOI: http://dx.doi.org/10.3126/jpan.v2i2.9729 J Psychiatrists’ Association of Nepal Vol.2, No.2, 2013 49-51